Diet-induced microbial adaptation process of red deer (Cervus elaphus) under different introduced periods - Guo, Jinhao; Jin, Yongchao; Tian, Xinmin; Bao, Heng; Sun, Yue; Gray, Thomas; Song, Yaqi; Zhang, Minghai (Frontiers in Microbiology, 2022)
Insufficient prey density is a major factor hindering the recovery of Amur tiger (Panthera tigris altaica), and in order to effectively restore the Amur tiger, red deer (Cervus elaphus) were released into the Huangnihe National Nature Reserve of Northeast China as the main reinforcement. Differences in feeding and synergistic changes caused by intestinal microbial community could impact the adaptation of wildlife following reintroductions into field environments. We analyzed the foraging change in shaping the intestinal microbial community of the red deer after being released to Huangnihe National Nature Reserve and screened the key microbial flora of the red deer when processing complex food resources. The feeding and intestinal microbial communities of the red deer were analyzed by plant DNA barcoding sequencing and 16S rRNA high-throughput sequencing respectively. The results showed that there were significant differences in food composition between wild and released groups [released in 2019(R2): n=5; released in 2021(R0): n=6), the wild group fed mainly on Acer (31.8%) and Abies (25.6%), R2 fed mainly on Betula (44.6%), R0 had not formed a clear preferred feeding pattern, but had certain ability to process and adapt to natural foods. Firmicutes (77.47%) and Bacteroides (14.16%) constituted the main bacterial phylum of red deer, of which the phylum Firmicutes was the key species of the introduced red deer for processing complex food resources (p < 0.05). The wild release process significantly changed the intestinal microbial structure of the red deer, making it integrate into the wild red deer. The period since release into the wild may be a key factor in reshaping the structure of the microbial community. This study suggested that the intestinal microbial structure of red deer was significantly different dependent upon how long since captive deer has been translocated. Individuals which have lived in similar environments for a long time will have similar gut microbes. This is adaption process of wildlife to natural environment after wild release, taking into account the gut microbes, the feeding changes in shaping microbial communities can help introduced red deer match complex food resources and novel field environments.